Jenis dan Klasifikasi Penjualan dalam Ekonomi Syariah: Types and Classification of Sales in Sharia Economics - rezki, rezki akbar norrahman (PT. PENERBIT TIGA MUTIARA, 2023)
Islamic economics has different principles from conventional economics, including in terms of sales contracts. In Islamic economics, there are several types of sales contracts used, such as bai' al-salam (future sales) and bai’ al-salam(manufacturing sales). Trust sales contracts are also important in ensuring transparency of the price of the goods or services sold. The research method uses descriptive qualitative in describing and explaining specifically with literature studies in data collection. The purpose of this research is to find out specifically about the types and qualifications of sharia sales that do not contain gharar and usury. In Islamic economics, payments in sales contracts can be deferred or paid in installments without involving interest or riba. This allows the buyer to pay according to an agreed schedule. Sales contracts in the Islamic economy differ from interest-bearing loan contracts, where there is an exchange of goods or services at a predetermined price. Islamic banks use sales contracts as a legitimate alternative to interest-bearing loan contracts, allowing them to provide financing that is fair and compliant with sharia principles. In the Islamic economy, there are also contracts for the sale of future commodities (salam), the sale of manufacturing (istisna'), and currency exchange (sarf). Islamic banks have an important role to play in facilitating these sales contracts, as intermediaries who ensure the contracts adhere to Shariah principles and meet applicable legal requirements. With a good understanding of the different types of these sales contracts, economic actors can choose the ones that suit their needs while complying with sharia principles.